2009
DOI: 10.1093/wber/lhp010
|View full text |Cite
|
Sign up to set email alerts
|

Political Accountability and Regulatory Performance in Infrastructure Industries: An Empirical Analysis

Abstract: The relationship between the quality of political institutions and the performance of regulation has recently assumed greater prominence in the policy debate on the effectiveness of infrastructure industry reforms. Taking the view that political accountability is a key factor linking political and regulatory structures and processes, this article empirically investigates its impact on the performance of regulation in telecommunications in time-series-cross-sectional data sets for 29 developing countries and 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 19 publications
0
47
1
2
Order By: Relevance
“…This might be due to the fact that most empirical studies have aggregated data on countries with different levels of development. Separating data according to GDP, Gasmi et al (2006) find a positive impact in data on developing countries and a negative impact in data on developed countries.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…This might be due to the fact that most empirical studies have aggregated data on countries with different levels of development. Separating data according to GDP, Gasmi et al (2006) find a positive impact in data on developing countries and a negative impact in data on developed countries.…”
Section: Resultsmentioning
confidence: 82%
“…In a previous econometric study (Gasmi et al, 2006), we have shown that political accountability is an important determinant of regulatory performance and forcefully argued that policies aimed at enhancing politically accountable systems should be given due attention in development programs. In this paper, we further investigate the relationship between the reforms of the telecommunications sector that have been actually implemented in developing countries and the evolution of this sector.…”
Section: Introductionmentioning
confidence: 92%
“…The first study concerning the impact of the quality of institutions on the performance of regulation, Gasmi et al (2006) is based on a set of regressions performed with two time-series-cross-sectional (TSCS) data samples, one containing information on 29 developing countries and another on 23 developed countries, and both covering the period that runs from 1985 to 1999, the last year for which data were available on all the variables considered in the study. For instance, licences are often granted conditional on the fulfilment of targets of penetration rates and quality and associated with exclusivity periods.…”
Section: Data and Econometric Methodologymentioning
confidence: 99%
“…44 This argument is spelled out by Bjorvatn and Soreide (2005). 45 For an overview of empirical evidence on how corruption influences performance through infrastructure procurement, see Della Porta and Vannucci (1999). 46 See also Hall (2007) concerning the experience of electricity private firms in Latin America.…”
Section: The Political Economy Of Reform For Infrastructure Performancementioning
confidence: 99%
“…44 Opportunities for corruption can be created in auctions, not only in the process of selecting the buyer of a public company (procurement), but also in negotiations about the concession terms and the mode of service provision. 45 The degree of responsibility on the part of the government versus the private sector -to cover unexpected costs or deficiencies in collected fees, for example-may be subject to for "corrupt trade." Firms may be encouraged to offer bribes to reduce their operational risk and thereby secure higher (expected) revenues.…”
mentioning
confidence: 99%